2019
DOI: 10.1007/s40145-019-0315-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of magnetoelectric effect in lead free K0.5Na0.5NbO3-BaFe12O19 novel composite system

Abstract: Lead-free magnetoelectric composites (1 ̶ x)K 0.5 Na 0.5 NbO 3 -(x)BaFe 12 O 19 (x = 30, 40, and 50 wt%) are synthesized using solid state reaction method. X-ray diffraction (XRD) patterns confirm formation of diphase composites. Field emission scanning electron microscopy (FE-SEM) gives information about grain size, connectivity, and microstructure of constituent phases. Dielectric parameters of composite samples are studied as a function of temperature and the transition temperatures corresponding to both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…This trend is expected to continue until frequencies close to 100 MHz, where the slowest and largest relaxation processes of the ionic liquid appear [41,49]. The MI coefficient obtained values are comparable, and even higher, than others obtained with recent composites based on multiaxial molecular-ionic ferroelectric/magnetostrictive materials [28] or ME composites [50,51], where values up to 186 mV cm −1 .Oe have been reported. Thus, our flexible and low cost developed structures based on non-polarized piezo-ionic/magnetostrictive materials open new perspectives in the development of advanced and functional composites for novel energy generation devices.…”
Section: Resultssupporting
confidence: 70%
“…This trend is expected to continue until frequencies close to 100 MHz, where the slowest and largest relaxation processes of the ionic liquid appear [41,49]. The MI coefficient obtained values are comparable, and even higher, than others obtained with recent composites based on multiaxial molecular-ionic ferroelectric/magnetostrictive materials [28] or ME composites [50,51], where values up to 186 mV cm −1 .Oe have been reported. Thus, our flexible and low cost developed structures based on non-polarized piezo-ionic/magnetostrictive materials open new perspectives in the development of advanced and functional composites for novel energy generation devices.…”
Section: Resultssupporting
confidence: 70%
“…BaM-based cationic substitutions for Fe 3+ are used to modify the dielectric and magnetic parameters, which play an important role in RL calculation. The substitutions for Fe 3+ of BaM-based can be divided into two main approaches: covalent cation substitution, such as Ga 3+ , In 3+ ; and Er 3+ and hetervalent cationic combination, such as Co 2+ -Ti 4+ , Co 2+ -Zr 4+ , and Ni 2+ -Ti 4+ [22][23][24][25][26]. However, recent studies have shown that the introduction of high-valence ions destroys the valence state equilibrium of barium ferrite, resulting in multiple absorption peaks, which can increase the bandwidth of electromagnetic wave absorption of the material [27][28][29].…”
Section: Introduction mentioning
confidence: 99%
“…3 So far, there were only limited numbers of studies on the CFO−KNN particulate composites, although pure or doped KNN and CFO have each been used frequently for making ME composites with other counterparts. 3,6,[11][12][13][14][15] Recently, computer simulation revealed that the composites made of KNN-based ferroelectrics and CFO-based ferrimagnets may potentially have high ME coefficients. 15…”
Section: Introductionmentioning
confidence: 99%